2020
DOI: 10.1002/ijgo.13470
|View full text |Cite
|
Sign up to set email alerts
|

Increased anxiety and depression in patients with gynecologic cancers during the COVID‐19 pandemic: A retrospective study from Japan

Abstract: Synopsis During the COVID‐19 pandemic, patients with cancer are susceptible to psychological stress, especially during cancer treatment. Timely evaluation is necessary to prevent psychological stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 5 publications
2
19
0
Order By: Relevance
“…with heterogeneous results that are difficult to compare (Agua et al, 2020;Letaief-Ksontini et al, 2020;Lou et al, 2020;Swainston et al, 2020; (Table 5). Most of these studies carried out on cancer patients have detected an increase in perceived levels of anxiety, depression, and global discomfort, highlighting the importance of the emotional sphere in their comprehensive treatment (Agua et al, 2020;Letaief-Ksontini et al, 2020;Lou et al, 2020;Swainston et al, 2020;van de Poll-Franse et al, 2020;Gultekin et al, 2021;Mogami et al, 2021). In our study it is striking how the greatest concern of oncology patients continues to be their tumor-even more than the COVID-19 pandemic itself.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…with heterogeneous results that are difficult to compare (Agua et al, 2020;Letaief-Ksontini et al, 2020;Lou et al, 2020;Swainston et al, 2020; (Table 5). Most of these studies carried out on cancer patients have detected an increase in perceived levels of anxiety, depression, and global discomfort, highlighting the importance of the emotional sphere in their comprehensive treatment (Agua et al, 2020;Letaief-Ksontini et al, 2020;Lou et al, 2020;Swainston et al, 2020;van de Poll-Franse et al, 2020;Gultekin et al, 2021;Mogami et al, 2021). In our study it is striking how the greatest concern of oncology patients continues to be their tumor-even more than the COVID-19 pandemic itself.…”
Section: Discussionmentioning
confidence: 51%
“…A 24-question semi-structured questionnaire was designed to measure clinical and sociodemographic variables and the exposure level to COVID-19. This questionnaire was designed considering possible risk factors related to elevated rates of emotional distress in cancer patients and based on previous clinical evidence (Agua et al, 2020;Letaief-Ksontini et al, 2020;Lou et al, 2020;Swainston et al, 2020;van de Poll-Franse et al, 2020;Gultekin et al, 2021;Mogami et al, 2021). The HADS (Hospital Anxiety and Depression Scale) questionnaire was used to measure variables related to psychological symptomatology.…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of this study revealed that the COVID-19 pandemic increased anxiety symptoms in cancer patients, with 61.5% exhibiting symptoms of anxiety. Consistently, several papers reported an increased risk of anxiety for cancer patients during the outbreak, varying from 19.1% in Singapore to 78% in the United States with many countries in between [13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 69%
“… 9 , 10 It has been shown that the disruption of medical activity in oncology, in addition to social isolation, fear of contagion, and economic constraints, has an impact on the psychophysical well‐being of cancer patients, with namely symptoms of depression, anxiety, and sleep disturbances. 11 , 12 , 13 , 14 , 15 More than 85% of cancer patients said they worried of cancer progression because of COVID‐19 pandemic. 11 Trust and proper communication by the medical team have a positive effect on worries related to the delay or interruption of treatment, but more than 80% of patients stated that they do not think the pandemic has changed treatment decisions by medical staff.…”
Section: Introductionmentioning
confidence: 99%